2021
DOI: 10.1002/aelm.202000823
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Manipulation of Electric Transport in MoTe2

Abstract: Layered semimetals such as monoclinic MoTe2 and WTe2 demonstrate superconducting, topological insulating, and Weyl semimetallic states based on their unique electronic band topology. While doping concentration, lattice constants, and spin–orbit coupling can largely modulate the quantum states of the semimetals, a puzzling issue is that their functional carrier density and magnetoresistance for practical applications critically vary by temperature, which cannot be explained by the conventional phonon effect or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Temperature alters the stacking order of TMDs. It has been reported that orthorhombic (T d ) and monoclinic (1T′) phases can be observed in MoTe 2 at different temperatures . Cheon et al reported that the 1T′ and T d phases have strong in-plane anisotropy in the interlayer coupling.…”
Section: Large-scale Phase Engineering Of 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature alters the stacking order of TMDs. It has been reported that orthorhombic (T d ) and monoclinic (1T′) phases can be observed in MoTe 2 at different temperatures . Cheon et al reported that the 1T′ and T d phases have strong in-plane anisotropy in the interlayer coupling.…”
Section: Large-scale Phase Engineering Of 2d Materialsmentioning
confidence: 99%
“…It has been reported that orthorhombic (T d ) and monoclinic (1T′) phases can be observed in MoTe 2 at different temperatures. 110 Cheon et al reported that the 1T′ and T d phases have strong in-plane anisotropy in the interlayer coupling. Thus, the energy required to slip the layer is small, 111 leading to such a unique stacking order transition.…”
Section: Phase Engineering By Thermodynamic Variablesmentioning
confidence: 99%
“…We explain the shift in critical V LG by the generation of Te vacancies during the liquid ionic gating, which induces electron doping. [ 32 ] Moreover, we can use a certain condition of liquid ionic gating to electrochemically etch the device channel (Figure S15, Supporting Information), further decreasing the critical V LG for phase transition.…”
Section: Polymorphic Memtransistor Based On Phase Transition Of Chann...mentioning
confidence: 99%
“…The native Tevacancy in semimetallic MoTe 2 is responsible for a temperature-manipulated transport in a manner equivalent to electrical gating. 34 Through precisely generating Te-vacancies with inducing electron-doping, the T d -MoTe 2−x samples show a promoted superconducting transition at 2.1 K compared with stoichiometric samples (no superconducting state down to 10 mK). 35 Also, the charge doping can modulate structural stability and induce phase transitions for layered MoTe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The lattice distortion associated with the difference in the atomic radius may also play some role in activating the EPC through exerting the strain. The native Te-vacancy in semimetallic MoTe 2 is responsible for a temperature-manipulated transport in a manner equivalent to electrical gating . Through precisely generating Te-vacancies with inducing electron-doping, the T d -MoTe 2– x samples show a promoted superconducting transition at 2.1 K compared with stoichiometric samples (no superconducting state down to 10 mK) .…”
Section: Introductionmentioning
confidence: 99%